Phylogenomic Analysis of R2R3 MYB Transcription Factors in Sorghum and their Role in Conditioning Biofuel Syndrome - Singh, Vinay; Kumar, Neeraj; Dwivedi, Anuj K.; Sharma, Rita; Sharma, Manoj K. (Current Genomics, 2020)
Background: Large scale cultivation of sorghum for food, feed, and biofuel requires concerted efforts for engineering multipurpose cultivars with optimised agronomic traits. Due to their vital role in regulating the biosynthesis of phenylpropanoid-derived compounds, biomass composition, biotic, and abiotic stress response, R2R3-MYB family transcription factors are ideal targets for improving environmental resilience and economic value of sorghum. Methods: We used diverse computational biology tools to survey the sorghum genome to identify R2R3-MYB transcription factors followed by their structural and phylogenomic analysis. We used inhouse generated as well as publicly available high throughput expression data to analyse the R2R3 expression patterns in various sorghum tissue types. Results: We have identified a total of 134 R2R3-MYB genes from sorghum and developed a framework to predict gene functions. Collating information from the physical location, duplication, structural analysis, orthologous sequences, phylogeny, and expression patterns revealed the role of duplications in clade-wise expansion of the R2R3-MYB family as well as intra-clade functional diversification. Using publicly available and in-house generated RNA sequencing data, we provide MYB candidates for conditioning biofuel syndrome by engineering phenylpropanoid biosynthesis and sugar signalling pathways in sorghum. Conclusion: The results presented here are pivotal to prioritize MYB genes for functional validation and optimize agronomic traits in sorghum.
Keywords: transcription factors